227k views
5 votes
Please tell me the answer to c ignore the question b thank you

Please tell me the answer to c ignore the question b thank you-example-1

2 Answers

5 votes

Answer:


\boxed{ z = 3m-2n}

Explanation:

=>
1000^m / 100^n

=>
(10)^(3m) / (10)^(2n)

Using rule of exponents
a^m/a^n = a^(m-n)

=>
10 ^(3m-2n)

Comparing it with
10^z, we get

=> z = 3m-2n

User Shubham Pandey
by
6.1k points
5 votes

Answer:

c).


{1000}^(m) / {100}^(n) \\ \\ {10}^(3m) / {10}^(2n)

Since they have the same base and are dividing we subtract the exponents

That's


{10}^(3m - 2n)

So

z = 3m - 2n

Hope this helps you

User Gabriel Cerutti
by
5.6k points